Fetal Pathology in an Aborted Holstein Fetus Infected With Bovine Parainfluenza Virus-3 Genotype A. Issue 2 (March 2019) - Macías-Rioseco, Melissa; Mirazo, Santiago; Uzal, Francisco A.; Fraga, Martín; Silveira, Caroline; Maya, Leticia; Riet-Correa, Franklin; Arbiza, Juan; Colina, Rodney; Anderson, Mark L.; Giannitti, Federico
Bovine parainfluenza virus-3 (BPIV-3) is a recognized respiratory pathogen of cattle, and it has also been identified in aborted fetuses. However, little is known of this agent as a reproductive pathogen and detailed descriptions of fetal pathology on natural cases are lacking in the scientific literature. This article describes and illustrates lesions in a fetus spontaneously aborted by a first-calving Holstein heifer, naturally infected with BPIV-3 genotype A, broadening the current knowledge on fetal pathology by this virus. Fetal autopsy revealed diffusely reddened, rubbery and unexpanded lungs. Histologically, there was necrotizing bronchiolitis/alveolitis with intraluminal fibrin exudate and syncytial cells in the bronchiolar/alveolar spaces, and non-suppurative peribronchiolitis and perivascular interstitial pneumonia. In the small intestine there was multifocal necrotizing cryptitis and occasional necrotic syncytial enterocytes. Intralesional and extralesional BPIV-3 antigen was detected by immunohistochemistry in the lung and small intestine, and BPIV-3a was identified in fetal tissues by RT-PCR and sequencing.